Identification of TDP-43 as an oncogene in melanoma and its function during melanoma pathogenesis. Issue 1 (2nd January 2017) - Zeng, Qinghai; Cao, Ke; Liu, Rui; Huang, Jinhua; Xia, Kun; Tang, Jintian; Chen, Xiang; Zhou, Ming; Xie, Huiqing; Zhou, Jianda
ABSTRACT: Background: Although recent studies have revealed TAR (trans-activating response region) DNA binding protein (TDP-43) as a potential therapeutic target for cancers, its role and clinical association with melanoma have not been explored. Objective: To identify the role and function of TDP-43 during melanoma pathogenesis. Methods: Firstly, the relationship between TDP-43 expression and patient survival was explored. Then TDP-43 expression level in melanoma tissue and different melanoma cell lines was measured. After silencing TDP-43 expression in melanoma cells, the impacts of TDP-43 on cellular proliferation, metastasis, glucose uptake, and glucose transporters levels were studied. In the end, effect of TDP-43 depletion on tumorigenicity of melanoma cells was tested in vivo. Results: Our results showed that TDP-43 was overexpressed in melanoma paraffin samples compared with that in nevi tissues. The high expression level of TDP-43 was associated with poor patient survival. By silencing TDP-43, we saw significant inhibition of cell proliferation and metastasis in A375 and WM451 cells. TDP-43 knockdown could suppress glucose transporter type-4 (GLUT4) expression and reduce glucose uptake. And downregulation of GLUT4 in melanoma cells induced inhibition of cell proliferation and metastasis. TDP-43 knockdown significantly slowed down tumor growth and decreased GLUT4 expression in vivo. Conclusion: TDP-43 is a novel oncogene in melanoma and regulates melanoma proliferation and metastasis potentially through modulation of glucose metabolism.